Communicative Linguistics as a Branch of Modern Linguistics - Ruziqulov Fazliddin; Botirova Gulsanam (Zien Journals, 2022)
This article is devoted to the emergence of communicative linguistics learning languages in real processes of interpersonal communication. The main tasks and directions of this branch of linguistics are considered. The important role of the functional approach to the language arising from the definition of its essence as a means of communication is emphasized.
Keywords: linguistics; communicative linguistics; approach; communication